Variability of essential oil composition of wormwood (Artemisia absinthium L.) affected by plant organ. Issue 1 (2nd January 2017) - Llorens-Molina, J. A.; Vacas, S.; Castell, V.; Németh-Zámboriné, É.
Abstract: The essential oil composition of leaves and roots of twenty individuals of wormwood ( Artemisia absinthium L.) belonging to different chemotypes has been investigated. They were obtained from two accesions coming from Hungarian and Spanish wild populations. Essential oils were extracted by hydrodistillation and analyzed by GC/MS and GC/FID. Results showed a great individual variability of wormwood accesions. Based on leaves, three chemotypes (sabinene + myrcene, β-thujone and new sesquiterpene type accounting up to 80.8% of sesquiterpenic fraction) were found in the Hungarian population and two chemotypes (( Z )-β-epoxyocimene and ( Z)- β-epoxyocimene + ( Z )-chrysanthemyl acetate types) were present in the Spanish one. The composition of EO of the roots from both locations was predominated by monoterpenic esters (14.5–80.2% and 59.9–90.3%, in Hungarian and Spanish samples respectively) but characteristic quantitative and qualitative differences were present. No relationship was found between the composition of EO of roots and leaves of the same plant.